HASIL BELAJAR KETERAMPILAN MENULIS KARANGAN DESKRIPSI DENGAN MODEL PEMBELAJARAN CONCEPT SENTENCE SISWA KELAS XI SEMESTER 2 SMA NEGERI 1 GEDANGAN - IRIANTI, YESI (LATERNE, 2018)
There are four kinds of language skill, such as listening, speaking, reading and writing. According to Nurgiyantoro (2010: 422), writing is the most difficult skill. The IX grade of language class in SMA Negeri 1 Gedangan get the average score of 75, lower than KKM. The Germany teacher give information that the students still have difficulty in pouring ideas in writing a description. Therefore, the research applied concept sentence learning model. In this learning model there are some keywords which used as concept in pouring ideas. According to Shabri Saleh (2015: 63), concept is an abstraction of an ideas with expressed in a word or symbol. This research question is “How the learning result of writing a description skill by using concept sentence learning model for the second semester student  XI grade students of SMA Negeri 1 Gedangan”. This research aim is “describing the learning result of writing a description skill with concept sentence learning model for the second semester student  XI grade students of SMA Negeri 1 Gedangan”. This research used descriptive qualitative approach. The datas were collected during four meetings. At the first time meeting, the average score was 69. Then the second meeting, the average score increased to 80. At the third meeting, it increased more to 82 until the fourth meeting became 85. Therefore, the concept sentence learning model can be applied in the German language learning because the students’s score result was increase  during three meetings. Keywords:  Learning Results, Writing Skills, Concept Sentence Learning Model